Utilizing test items analysis to examine the level of difficulty and discriminating power in a teacher-made test - Sayit Abdul Karim; Suryo Sudiro; Syarifah Sakinah (EduLite: Journal of English Education, Literature and Culture, 2021)
Apart from teaching, English language teachers need to assess their students by giving a test to know the students’ achievements. In general, teachers are barely conducting item analysis on their tests. As a result, they have no idea about the quality of their test distributed to the students. The present study attempts to figure out the levels of difficulty (LD) and the discriminating power (DP) of the multiple-choice (MC) test item constructed by an English teacher in the reading comprehension test utilizing test item analysis. This study employs a qualitative approach. For this purpose, a test of 50-MC test items of reading comprehension was obtained from the students’ test results. Thirty-five students of grade eight took part in the MC test try-out. They are both male (15) and female (20) students of junior high school 2 Kempo, in West Nusa Tenggara Province. The findings revealed that16 items out of 50 test items were rejected due to the poor and worst quality level of difficulty and discriminating index. Meanwhile, 12 items need to be reviewed due to their mediocre quality, and 11 items are claimed to have good quality items. Besides, 11 items out of 50 test items were considered as the excellent quality as their DP scores reached around 0.44 through 0.78. The implications of the present study will shed light on the quality of teacher-made test items, especially for the MC test.